Reflectance based optical fibre sensor for ammonium ion using solid-state Riegler's reagent - Ling, TL; Ahmad, M; Heng, LY (Elsevier Science Sa, 2024)
A new optical sensor for fast screening of ammonium (NH4+) ion was developed based on immobilisation of p-nitrobenzene-diazonium chloride (Riegler's reagent) onto XAD-7 microbeads. In aqueous solution, the diazonium salt is unstable and will spontaneously decompose at room temperature but we have successfully stabilised this compound via immobilisation using physical adsorption to create a solid-state Riegler's reagent for NH4+ ion determination with a storage period of one month. The quantification of NH4+ ion concentration was possible by using reflectance spectrophotometry method with an optical fibre probe. The solid-state Riegler's reagent based optical sensor yielded a wide linear response range for NH4+ ion of 10-60 ppm and a fast response time of 2 min when compared with many commonly used coloured reagents. The limit of detection (LOD) of the optical NH4+ ion sensor was 7.9 ppm NH4+ ion with optimum response at pH 7. The response of the sensor was reproducible (4.2-5.7% relative standard deviation, n = 3) and can be regenerated using buffer pH 1. Except for Fe3+ ions, most common ions showed no serious interference. The sensor was also used for the determination of NH4+ ion in river water and the results obtained were comparable to those obtained by a standard titrimetric method. (c) 2012 Elsevier B.V. All rights reserved.